The Associative Changes in Scutellum Nuclear Content and Morphology with Viability Loss of Naturally Aged and Accelerated Aging Wheat (Triticum aestivum) Seeds - Ahmed, Zaheer; Yang, Hui; Fu, Yong-Bi (Frontiers in Plant Science, 2016)
Timely prediction of seed viability loss over long-term storage represents a challenge in management and conservation of ex situ plant genetic resources. However, little attention has been paid to study the process of seed deterioration and seed ageing signals under storage. An attempt was made here to investigate morphological and molecular changes in the scutellum and aleurone sections of naturally or artificially aged wheat seeds using TUNEL assay and DAPI staining. Twelve wheat genotypes or samples exposed to naturally ageing (NA) or accelerated ageing (AA) were assayed and these samples had germination rates ranging from 11 to 93%. The assayed samples showed substantial changes in scutellum, but not aleurone. The nuclei observed in the majority of the scutellum cells of the NA seed samples of lower germination rates were longer in size and less visible, while the scutellum cell morphology or arrangement remained unchanged. In contrast, longer AA treatments resulted in the loss of scutellum cell structure, collapse of cell layers, and the disappearance of honey comb arrangements. These nuclei and structural changes were consistent with the DNA assessments of nuclear alternations for the selected wheat samples. Interestingly, the sample seed germination loss was found to be associated with the reductions in the scutellum nuclear content and with the increases in the scutellum nuclei length to width ratio. These findings are significant for understanding the process of wheat seed deterioration and are also useful for searching for sensitive seed ageing signals for developing tools to monitor seed viability under storage